Comfort, Christ and man's best friend: The 'new' Christian role for therapy dogs. Issue 6 (November 2017) - Holt, Nicole; Walker, Peter
This article has been designed to provide a theological context for already existing research in the field of therapy dogs and their religious utilization. It also aims to set the scene for future research concerning the relationship between dogs and Christianity and between health, wellbeing and spirituality. This article argues the strengths of comfort companions and maintains that even through the potential ethical concerns, such practices show a resurgence in innovative thought and practice which aims to address psychological and physiological dimensions to the human condition which might be addressed through natural means, rather than medication. Dogs are already making their way into Christian churches and wider spiritual practices, so it may not be long before 'comfort dogs' arrive from America.